Modulation of Tyrosine Hydroxylase, Neuropeptide Y, Glutamate, and Substance P in Ganglia and Brain Areas Involved in Cardiovascular Control after Chronic Exposure to Nicotine - Merari F. R. Ferrari; Emerson F. Coelho; Karen L. G. Farizatto; Gerson Chadi; Debora R. Fior-Chadi (International Journal of Hypertension)
Considering that nicotine instantly interacts with central and peripheral nervous systems promoting cardiovascular effects after tobacco smoking, we evaluated the modulation of glutamate, tyrosine hydroxylase (TH), neuropeptide Y (NPY), and substance P (SP) in nodose/petrosal and superior cervical ganglia, as well as TH and NPY in nucleus tractus solitarii (NTS) and hypothalamic paraventricular nucleus (PVN) of normotensive Wistar Kyoto (WKY) and spontaneously hypertensive rats (SHR) after 8 weeks of nicotine exposure. Immunohistochemical and in situ hybridization data demonstrated increased expression of TH in brain and ganglia related to blood pressure control, preferentially in SHR, after nicotine exposure. The alkaloid also increased NPY immunoreactivity in ganglia, NTS, and PVN of SHR, in spite of decreasing its receptor (NPY1R) binding in NTS of both strains. Nicotine increased SP and glutamate in ganglia. In summary, nicotine positively modulated the studied variables in ganglia while its central effects were mainly constrained to SHR.